Concerns of Infertile Women Candidates for Egg Donation: A Qualitative Study - Maryam Bagheri; Mina Jafarabadi; Seyedeh Fatemeh Vasegh Rahimparvar; Ahmad Ali Nourbala; Zahra Behboodi Moghadam (Tehran University of Medical Sciences, 2020)
Objective: Women with premature ovarian insufficiency, menopause, gonadal dysgenesis, and genetic disorders as well as those with a history of recurrent in vitro fertilization failure may benefit from the assisted fertility techniques. These women experience concerns that directly affect their married life especially in egg donation treatment. This study was conducted to investigate the reproductive health concerns of infertile women who were candidates for egg donation. Materials and methods: This qualitative content analysis was conducted in 17 infertile women who were referred to Imam Khomeini Hospital Infertility Clinic from July 2018 to March 2019. The participants were selected through purposeful sampling. Data were collected through individual in-depth semi-structured interviews. A conventional qualitative content analysis approach was adopted for data analysis using the MAXQDA12 software. Results: The results of data analysis showed five themes, including threatened married life, lack of supportive situation, religious beliefs, psychosocial damage, and damaged feminine identity. Conclusion: Infertility is usually accompanied by a great psychological sadness referred to as "stress of infertility". Assisted reproductive techniques (ART) are also a source of stress for patients; therefore, it has a significant impact on the marital relationship and mental health of infertile women. Hence, there is a need for psychological support from the treatment team to reduce woman reproductive health concerns.